Implementation of Leadership Strategies and Work Commitments in Maintaining Employee Performance in CV. Silvana Print & Advertising Kendari City Southeast Sulawesi - Muhamad Masri (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The purpose of this study was to determine the description of the application of leadership strategies and work commitments of CV. Silvana Print & Advertising in maintaining employee performance. Data collection methods used was observation, open interview, and documentation. Analysis of the data in this research is a qualitative descriptive analysis through case studies. Based on the results of the study note that the leadership strategy and work commitment in maintaining employee performance on the CV. Silvana Print & Advertising is done by controlling employees every day either directly or indirectly. Control is carried out related to the production process, optimizing the use of raw materials. Besides, leaders always provide ideas, instructions, and provide solutions to employees who have problems or obstacles, and leaders also use the WhatsApp group as a media to help communicate with employees. Work commitment, the company applies work standards that can improve the quality of employees and pay attention to employee needs ranging from the needs of life, the needs of employees in production activities. Employee performance, in maintaining the company's employee performance, pay attention to the portion of work and ability of employees, ranging from the ability to initiate employees themselves, employee adaptation, creativity, discipline, experience, and employee cooperation.